Management of Endovascular Treatment for Acute Ischemic Stroke During the COVID-19 Pandemic at a Single Institution in Beijing, China: A Brief Report. Issue 3 (July 2021) - Li, Shu; Zeng, Min; Dong, Jia; Li, Muhan; Yan, Xiang; Li, Ruowen; Zhang, Yuewei; Huo, Xiaochuan; Miao, Zhongrong; Wang, Shuo; Peng, Yuming; Han, Ruquan
Abstract : Background: The coronavirus disease (COVID-19) pandemic is currently a major challenge for health care systems around the world. For a time-sensitive emergency such as acute ischemic stroke (AIS), streamlined workflow times are essential to ensure good clinical outcomes. Methods: The aim of this single-center, retrospective, observational study was to describe changes in stroke workflow patterns and clinical care during the COVID-19 pandemic. Data from AIS patients undergoing emergent endovascular treatment (EVT) between 23 January and 8 April 2020 were retrospectively collected and compared with data from patients admitted during a similar period in 2019. The primary outcome was difference in time from symptom onset to recanalization. Secondary outcomes included workflow times, clinical management, discharge outcomes, and health-economic data. Results: In all, 21 AIS patients were admitted for emergent EVT during the 77-day study period, compared with 42 cases in 2019. Median time from symptom onset to recanalization was 132 minutes longer during the pandemic compared with the previous year (672 vs. 540 min, P =0.049). Patients admitted during the pandemic had a higher likelihood of endotracheal intubation (84.6% vs. 42.4%, P <0.05) and a higher incidence of delayed extubation after EVT (69.2% vs. 45.5%, P <0.05). National Institutes of Health Stroke Scale at hospital discharge was similar in the 2 cohorts, whereas neurointensive care unit stay was longer in patients admitted during the pandemic (10 vs. 7 days, P =0.013) and hospitalization costs were higher (123.9 vs. 95.2 thousand Chinese Yuan, P =0.052). Conclusion: Disruptions to medical services during the COVID-19 pandemic has particularly impacted AIS patients undergoing emergent EVT, resulting in increased workflow times. A structured and multidisciplinary protocol should be implemented to minimize treatment delays and maximize patient outcomes.